Penerapan PSAK 69: Biological Asset Intensity, Growth, Leverage, dan Opini KAP Terhadap Pengungkapan Aset Biologis - Adinda Dwi Putri; Asriani Junaid; Ummu Kalsum (Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2023)
This study aims to examine the application of PSAK 69 in relation to Biological Asset Intensity, Growth, Leverage, and Auditor Opinion (KAP) on the Disclosure of Biological Assets. The research uses secondary data in the form of quantitative data obtained from the Indonesia Stock Exchange (IDX) at the Capital Market Investment Gallery of the Faculty of Economics and Business, Universitas Muslim Indonesia. The study population includes agricultural companies in the sub-industries of plantations and food crops listed on the IDX during the period of 2021-2023, totalling 36 companies. The sample was selected using purposive sampling, and 17 companies met the research criteria, with a three-year observation period. The research findings indicate that biological asset intensity has a positive but insignificant effect on the disclosure of biological assets, suggesting that a higher proportion of biological assets within a company does not necessarily lead to increased information transparency. Meanwhile, the variable of growth, leverage, and auditor opinion have a significant positive effect on the disclosure of biological assets, implying that external and reputational factors encourage companies to be more transparent in disclosing information related to biological assets in their financial statements